Research on the mechanism how consumer expected regret affects market access for pirated information products - Jia Xue; Peng Gao; Youshi He; Zhiwen Li; Hanyang Xu (PLoS ONE, 2026)
In the past, traditional supervision of pirated information products mostly adopted a post incident disposal model. Under the supervision of government departments and the continuous improvement of manufacturer product quality, the gap in quality and user experience between genuine and pirated products is expanding, thereby curbing the spread of pirated products. At present, with the emergence of cloud services, the spread of information products has changed from offline physical transactions to online digital services, and the sales model has changed from a one-time buyout to a subscription system of continuous payment. In this new context, there have been significant changes in the attributes of pirated information products and customer consumption patterns. The utility analysis model of quality preference and law enforcement supervision may not be well adapted in some cases. However, this study introduces regret theory and expected regret parameters to construct an impact analysis model on the market access of pirated information products, which is closer to the behavioral decision-making patterns of consumers in cloud service scenarios. The conclusion of this study indicates that customers’ sensitivity to expected regret directly affects the quality and price decisions of product manufacturers. The expected regret negative effect of pirated products also provides a more scientific basis for piracy regulation. Appropriate expected regret is not only beneficial for increasing legitimate consumer surplus and product manufacturer profits, but also promotes an increase in overall social welfare.